PEMBINAAN SKILL PEMBUATAN MASKER WAJAH HERBAL KEPADA SISWA SMK UNGGULAN HUSADA MELALUI PERAN DOSEN SEBAGAI GURU TAMU - Muliyani Muliyani; Nazhipah Isnani; Muhammad Zaini; Iqlima Iqlima; Popong Nur Apipah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Vocational education directs students to work in the industry with the skills they have in accordance with the abilities they take in the vocational education. Many problems have happened to students lately and another problem is the lack of adequate practice facilities. Various efforts and efforts must be made by schools to overcome this problem, among others, by fulfilling the necessary facilities through self-help and requests for assistance for facilities and teacher training to the central and regional governments. In the problems above, there are problems that occur in education, especially in SMK Unggulan Husada Banjarmasin, namely the management in the field of entrepreneurship which still needs refreshment to be able to implement the business that will be run from the skills possessed by students, especially the pharmacy department. So, there is a need for the dedication of lecturers who act as guest teachers. The learning method is known as a guest teacher or an outsider who is not a teacher giving lessons to students in order to overcome the backwardness of technology and learning facilities. The Resources Person (Guest Teacher) learning method is based on resource-based learning. Learning outcomes have increased after being given motivations and very enthusiastic during practical tutoring.